2006
DOI: 10.1016/j.jtcvs.2005.10.047
|View full text |Cite
|
Sign up to set email alerts
|

En bloc rotation of the truncus arteriosus—an option for anatomic repair of transposition of the great arteries, ventricular septal defect, and left ventricular outflow tract obstruction

Abstract: All patients survived the procedure. In patient 3 (a neonate), the chest was left open for 2 days because of capillary leakage and From the Department of Cardiac Surgery, General Hospital Linz, a and the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…The addition of the autograft half rotation, the arterial switch, the Lecopmpte maneuver, and preserved pulmonary valves are the main technical features that differentiate from the Nikaidoh procedure. The procedure of en bloc half rotation of the truncus arteriosus plus arterial switch has the following advantages [7,12]. First, the LVOTO is entirely avoided because the translocated aorta is directly over the LVOT which is enlarged by a U-shaped VSD patch.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the autograft half rotation, the arterial switch, the Lecopmpte maneuver, and preserved pulmonary valves are the main technical features that differentiate from the Nikaidoh procedure. The procedure of en bloc half rotation of the truncus arteriosus plus arterial switch has the following advantages [7,12]. First, the LVOTO is entirely avoided because the translocated aorta is directly over the LVOT which is enlarged by a U-shaped VSD patch.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies report on 1 technique. 8,9,[13][14][15][16][17][18][19][20] Some studies report outcomes of different procedures in a single center, 10,21,22 whereas 1 multicenter study reports on different operations. 23 All of the studies were retrospective, and none of the studies were randomized.…”
Section: Resultsmentioning
confidence: 99%
“…More radical techniques have been reported by Yamagishi and by Mair: an autologous half-turned truncal block that involves both semilunar valves is fully detached from the heart and turned 180°before it is re-inserted with the aortic valve on top of the LVOT and the pulmonary valve over the RVOT. 8,9 The "en bloc rotation" technique provides sufficient length of the autologous pulmonary posterior wall for direct anastomosis by itself. The risk of late right ventricular outflow tract obstruction (RVOTO) is thought to be reduced by elimination of the extracardiac conduit and by having a fully tubular pulmonary trunk or at least a posterior wall of native tissue.…”
Section: Posterior Aortic Translocation and "En Bloc Rotation" Technimentioning
confidence: 99%
See 1 more Smart Citation
“…The growth potential of the PA is maintained. Several reports have shown that the growth of tubular structures as well as the functions of both semilunar valves were preserved and showed harmonious growth in the late phase [25][26][27]. Overstretch or distortion of the coronary arteries does not occur, unlike in the Nikaidoh procedure [23,28], taking into consideration the posterior transference distance of the aortic valve according to the degree of PS.…”
Section: Commentmentioning
confidence: 99%